2010
DOI: 10.1016/j.jvs.2010.06.135
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Aspirate Concentrate in Critical Limb Ischemia: Results of a Multicenter Randomized Double-Blind Trial

Abstract: true2016-03-16T16:38:26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Harvest Trial collected 240 mL of bone marrow that was concentrated and injected into the ischemic extremity, similar to that in this report. 8 These investigators found that freedom from major amputation in patients who presented with tissue loss was 61% in cell therapy patients vs 29% in placebo-treated patients. The RESTORE-CLI trial randomized patients to expanded autologous cell therapy vs placebo in no-option CLI patients 9,10 ; 50 mL of bone marrow was harvested, and cells were then sent to the sponsor, who expanded specific cell lines in a bioreactor for 2 weeks, after which the cells were returned to the site and injected into the limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Harvest Trial collected 240 mL of bone marrow that was concentrated and injected into the ischemic extremity, similar to that in this report. 8 These investigators found that freedom from major amputation in patients who presented with tissue loss was 61% in cell therapy patients vs 29% in placebo-treated patients. The RESTORE-CLI trial randomized patients to expanded autologous cell therapy vs placebo in no-option CLI patients 9,10 ; 50 mL of bone marrow was harvested, and cells were then sent to the sponsor, who expanded specific cell lines in a bioreactor for 2 weeks, after which the cells were returned to the site and injected into the limb.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several phase 2 clinical trials that have demonstrated promising outcomes in patients with CLI compared with placebo. 810 This was especially true in patients who presented with tissue loss. 3 These trials have used a single set of intramuscular injections of autologous cells obtained from either bone marrow harvest or expanded cell lines after aspiration.…”
mentioning
confidence: 99%